1998
DOI: 10.1086/ntj41789363
|View full text |Cite
|
Sign up to set email alerts
|

Flat Taxes and Effective Tax Planning

Abstract: Stiglitz (1985) shows that income deferral opportunities and differentially taxed economic activities provide incentives for investors to engage in tax avoidance strategies. In this paper, I describe several tax avoidance strategies that can be used by taxpayers in a Hall-Rabushka flat tax system to reduce or eliminate their tax liabilities. Effective tax planning continues to be viable in a flat tax regime because the idealized environment envisioned by the proposal does not consider taxpayers' strategic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…The resultant effects are tax payments that are lower than the statutory tax rates. Consistent with the finding in this study, Calegari (1998) reported that income deferral opportunities or tax-exempt incomes are incentives for organizations to engage in tax avoidance.…”
Section: Results and Analysissupporting
confidence: 89%
“…The resultant effects are tax payments that are lower than the statutory tax rates. Consistent with the finding in this study, Calegari (1998) reported that income deferral opportunities or tax-exempt incomes are incentives for organizations to engage in tax avoidance.…”
Section: Results and Analysissupporting
confidence: 89%